Current Account Deficit in Turkey: Cyclical or Structural? - Hakan Kara; Çağrı Sarıkaya (Koç University-TÜSİAD Economic Research Forum (ERF), 2014)
Turkey's high current account deficit has been at the core of macroeconomic policy discussions in recent years. Quantifying the role of cyclical factors in driving the current account fluctuations is essential for designing an appropriate policy response and evaluating the impact of policy measures. Using a simple methodology, this study extracts the cyclical component of the current account in Turkey, with special reference to its three main drivers; namely foreign demand, domestic demand and foreign trade prices. We argue that the underlying (cyclically-adjusted) current account deficit has displayed a persistent deteriorating trend during 1998-2007 period before stabilizing around 6 percent of GDP in recent years. Decomposing the current account deficit into cyclical and non-cyclical factors allows us to assess the impact of recent policy actions. Our computations suggest that, although the policies pursued by the central bank and other authorities since 2011 have removed the cyclical part to a great extent, there remains a sizeable component of the deficit to be dealt with more structural policies.
Keywords: E32; F14; F32; 330; Current Account Balance; Foreign Trade; Business Cycle; Cyclical Adjustment; Filtering